Оцінка податкових надходжень від використання лісових землекористувань в умовах децентралізації влади - Openko, Ivan; Stepchuk, Yanina; Tsvyakh, Oleg (Dr. Viktor Koval, 2019)
Introduction. The financial and economic mechanism rational use and protection of land forestry should be based on realization national land relations policy, which envisages comprehensive state support for efficient use of nature through financing of appropriate organizational measures and introduction of economic instruments, incentives for rational use of forest resources. The main levers of such a mechanism are fiscal, monetary, budgetary and other elements of influence on economic entities. Aims and tasks. To realization the delivered goal it is necessary to solve a number of tasks, namely: to determine the actual area of forest land within the respective united territorial communities in Ukraine, to determine the possible economic income from the use of these forested areas, to calculate the volumes of fiscal receipts to the budgets of united territorial communities from forestry enterprises. Results. With the help of geoinformation approach was installed, it was established that the forest area in the united territorial communities were concentrated in Zhytomyrskа (788.5 thousand ha), Chernihivska (583.6 thousand ha), Volynska (432.9 ha), Rivnenska (282, 8 thousand hectares), Sumska (216,0 thousand hectares) regions. Whereas the smallest forest area within the boundaries of the united territorial communities is concentrated in Kirovohradska, Zakarpatska, Mykolaivska, Zaporizka, Vinnytska, Donetska, Luhanska, Odeska, Khersonska regions. Conclusions. Besides, in the case of use of forest areas within united territorial communities utility companies, they pay 18% income tax, which comes fully to the budget of the united territorial communities. We have made calculation of such fiscal receipts by areas where forestry production it is profitable. Therefore, our proposed scientific approach to the development of a financial and economic mechanism for regulating the rational use of forest land use should be based on the totality of fiscal budgetary relationships between forest resources and subjects entrepreneurial activity, which are based on the application of the geospatial approach of accounting of forest areas as an integral part of information support for the effective functioning of the economic system as a whole. On the whole, due to the proposed financial and economic mechanism, the total amount of tax revenues to united territorial communities in Ukraine can be increased by 10.2% of the actual receipts from their own resources of the united territorial communities in Ukraine for 2015 – 2016, or 6.01% of total volume taxes on individuals' income the united territorial communities in 2018. At the same time, the forest area within the united territorial communities at the national level is only 18.95% as of 2019.